Analisis Pemilihan Moda Transportasi Bagi Mahasiswa Universitas Sultan Ageng Tirtayasa - Priambodho, Bambang Adhi; Asyiah, Siti; Bethary, Rindu Twidi; Setiawati, Dwi Novi; Takimai, Kristina (Universitas Ibn Khaldun, 2025)
Sultan Ageng Tirtayasa University (Untirta) has an increasing number of students every year, causing traffic jams. One way to overcome this problem is to know the characteristics of student movements in traveling, especially in choosing the mode of transportation to be used. This study aims to observe the characteristics of transportation users traveling to campus and to analyze a mode selection model.This research was conducted with data from observations, questionnaire results, literature review, and data processing using the SPSS program with the Stated Preference method and the binomial logit model. The attributes used are cost (X1), travel time (X2), service convenience (X3), safety and security (X4). The results of the survey data The characteristics of the respondents in this study were 68% of the respondents were female with the majority of the age range 21-23 years as much as 71%, more respondents traveled to campus in 20-40 minutes by 46%, the mode of transportation most often used to visit campus is a motorcycle, reaching 54%. Travel time is the factor that most influences the choice of mode of transportation. The reason for choosing a mode is that many respondents choose a mode of transportation based on the fare attribute for private transport, namely 72.1% and for public transportation, namely 27.9%. Based on the time attribute, the probability of students choosing private transportation is 71.2% and public transportation is 28.8%. Based on the convenience attribute, the probability of students choosing private transportation is 71.6% and public transportation is 28.4%. Based on safety and security attributes, the probability of students choosing private transportation is 74% and public transportation is 26%.